UNDERSTANDING THE DISEASE COURSE OF PATIENTS WITH COVID-19 AND TYPE 2 DIABETES: A SCOPING REVIEW - Ahmad Hasyim Wibisono; Ayu Nanda Lestari; Ahmad Jamaluddin (Jurnal Kesehatan, 2023)
Background: The outbreak of Covid-19 since it was first identified in Wuhan has a tremendous global effect on many aspects of human life and it affects both developed and developing countries. Meanwhile, the prevalence of diabetes is also increasing along with the viral infection, hence, a review needs to be developed that can serve as the basis for clinical care improvements. Design and methods: This scoping study review aims to explore the relationship between diabetes and Covid-19 condition using the latest relevant evidence. Results: The findings revealed that after hypertension and cardiovascular diseases, diabetes is a major comorbid among patients with the virus. Based on the existing evidence, the comorbid disease has deleterious effects on the treatment course, morbidity, and clinical outcomes of Covid-19. Furthermore, some unique changes in immune responses have been identified, which exhibit different manifestations and interactions with standard diabetes treatments. Interactions have also been discovered between blood glucose, body mass index, and several hematological parameters, which correspond to the progression of the infection among diabetic patients. Conclusion: Based on the results, Covid-19 triggered an exponential rise in the systemic inflammatory reaction, and patients with diabetes tend to have worse conditions, which were indicated by the increase in the ICU admission and mortality rate. Furthermore, the viral infection has various effects on the blood glucose stability of patients.